The Effectiveness of Loose Parts Media in Enhancing Early Childhood Creativity - N. Nanti; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to determine the effectiveness of loose parts media in enhancing early childhood creativity at Tunas Harapan Kindergarten. The research employs a mixed-methods approach, using a quasi-experimental design with a non-equivalent control group for the quantitative data, and interviews with the principal, teachers, and parents as supporting qualitative data. The research subjects were children aged 5–6 years, divided into an experimental group and a control group. Children’s creativity was measured using an observation checklist based on indicators of fluency, flexibility, originality, and elaboration. The results show that the average creativity score of the experimental group increased significantly from 59.40 in the pretest to 83.20 in the posttest, while the control group only increased from 60.10 to 69.30. The results of the independent sample t-test show a significance value of 0.000 < 0.05, indicating a significant difference in creativity improvement between the two groups. The qualitative findings support the quantitative results, showing that children became more enthusiastic, actively explored, and were able to collaborate with their peers. Based on these findings, it can be concluded that loose parts media is effective in enhancing early childhood creativity and can be used as an innovative, child-centered learning strategy.